A Common Language among Child, School and Parents: The Use of Pedagogical Documentation in the Parent Involvement Process - Selda ARAS; Figen ŞAHİN; Arif YILMAZ; Ayça ÜLKER (Anı Publishing, 2021)
This study aims to examine the role of pedagogical documentation as a part of the school-parent collaboration from the perspectives of parents. In this study, which was conducted with the phenomenological design, data were collected using semi-structured interviews from 27 parents. The findings of the inductive analyzes were gathered under the themes of the visibility of learning, the parent-school bridge, and the child-parent-teacher collaboration. In line with the perceptions and experiences of parents, the findings showed that the pedagogical documentation increases the awareness of parents about their child's learning experiences at school, interactions, and reflections on these, provides guidance about parenting, improves the interaction between child and parents, supports the development of the child and learning at home, and contributes to school-parent collaboration. Given the contribution of parent involvement on child development and learning, it is believed that the findings obtained in this study will contribute to teachers, policymakers, and program developers in terms of utilizing pedagogical documentation as a tool for school-home collaboration.